Outcomes and prognostic factors in initially unresectable hepatocellular carcinoma treated using conversion therapy with lenvatinib and TACE plus PD-1 inhibitors - Li, Xingzhi; Chen, Jie; Wang, Xiaobo; Bai, Tao; Lu, Shaolong; Wei, Tao; Tang, Zhihong; Huang, Chengwen; Zhang, Bin; Liu, Bowen; Li, Lequn; Wu, Feixiang (Frontiers in Oncology, 2023)
Purpose: To evaluate the outcomes and prognostic factors for patients using conversion therapy with lenvatinib combined with transcatheter arterial chemoembolization (TACE) plus programmed cell death protein-1 (PD-1) inhibitors (LTP) for initially unresectable hepatocellular carcinoma (iuHCC). Methods: Data on 94 consecutive patients with iuHCC who received LTP conversion therapy from November 2019 to September 2022 were retrospectively analyzed. Early tumor response was reported when patients showed complete or partial response at the time of their first follow-up (4–6 weeks) after initial treatment, in accordance with mRECIST. The endpoints consisted of conversion surgery rate, overall survival (OS), and progression-free survival (PFS). Results: Early tumor response was found in 68 patients (72.3%) and not in the remaining 26 patients (27.7%) in the entire cohort. Early responders had a significantly higher conversion surgery rate than non-early responders (44.1% vs. 7.7%, p=0.001). Early tumor response was the only factor independently associated with successful conversion resection, as indicated by multivariate analysis (OR=10.296; 95% CI: 2.076–51.063; p=0.004). Survival analysis showed that early responders had longer PFS (15.4 vs. 7.8 months, p=0.005) and OS (23.1 vs. 12.5 months, p=0.004) than non-early responders. Early responders who underwent conversion surgery also had significantly longer median PFS and OS (not reached, not reached) than those who did not (11.2 months, p=0.004; 19.4 months, p<0.001). In multivariate analyses, early tumor response was identified as an independent prognostic factor for longer OS (HR=0.404, 95% CI: 0.171–0.954; p=0.039). Successful conversion surgery was also an independent predictive factor for longer PFS (HR=0.248, 95% CI: 0.099–0.622; p=0.003) and OS (HR=0.147, 95% CI: 0.039–0.554; p=0.005). Conclusions: Early tumor response is an important predictive marker for successful conversion surgery and prolonged survival in patients with iuHCC treated using LTP conversion therapy. Conversion surgery is necessary to improve survival during conversion therapy, particularly for early responders.